Green synthesis of novel polyoxoanions of tungsten containing phosphorus as a heteroatom: characterization, non-isothermal decomposition kinetics and photocatalytic activity - D'Cruz, Bessy; Samuel, Jadu; Sreedhar, Mulloor Kesavapillai; George, Leena (New Journal of Chemistry, 2014)
Synthesis of cetylpyridinium phosphotungstate (CPW) nanospheres was carried out by using sodium tungstate and a structure directing cationic surfactant, cetyl pyridinium chloride (CPC), at room temperature by applying green chemistry principles. The composition and morphology of the nanospheres were established by Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), atomic force microscopy (AFM), thermogravimetric analysis (TGA) and inductively coupled plasma atomic emission spectroscopic (ICP-AES) techniques. Thermal properties of the nanoparticles were investigated by nonisothermal analysis under a nitrogen atmosphere at four different heating rates 10, 15, 20 and 25 degrees C min(-1). The thermal decomposition of CPW occurred in two stages. The activation energy values at each stage of thermal decomposition for all heating rates were calculated by Flynn-Wall-Ozawa (FWO) and Kissinger-Akahira-Sunnose (KAS) methods. The invariant kinetic parameter (IKP) method and the master plot method were also used to evaluate the kinetic parameters and mechanism for the thermal decomposition of CPW. The photocatalytic water oxidation mechanism using a CPW catalyst in the presence of a platinum (Pt) co-catalyst enhances the H-2 evolution, which was found to be 2.0 mmol g(-1) h(-1).